Improving the rheological and filtration properties of an invert emulsion mud using a locally sourced modified polymer (2022)
Drilling fluid is designed for easy to use, cost effective and environmentally friendly. Several studies have been carried out on the use of local materials such as starch as suitable substitute for imported additives. Due to this short coming resulting from the use of native starch, the potatoes starch was chemically modified using the process of graft copolymerization, before being investigated as an additive for treatment of invert emulsion drilling. Three mud samples labelled (Base fluid, Copolymer 1 and Copolymer 2) were prepared and diesel labelled Base fluid served as control. Varying concentration of additives (1.0 and 2.0 g) were used at added to the different mud samples and laboratory study was carried out using the API Recommended Practice at varying temperature. This study is aimed at improving the properties of an invert emulsion mud using chemically modified locally sourced pomoea batatas as additive